Association of lecithin-cholesterol acyltransferase activity and low-density lipoprotein heterogeneity with atherosclerotic cardiovascular disease risk: a longitudinal pilot study - Katsuaki Yokoyama; Shigemasa Tani; Rei Matsuo; Naoya Matsumoto (BMC Cardiovascular Disorders, 2018)
Abstract Background Lecithin-cholesterol acyltransferase (LCAT) is believed to be involved in reverse cholesterol transport, which is known to play a key role in suppression of atherosclerosis. However, recent investigations have demonstrated that higher LCAT activity, measured in terms of the serum cholesterol esterification rate by an endogenous substrate method, is associated with increased formation of triglyceride (TG)-rich lipoproteins (TRLs), leading to a decrease in the low-density lipoprotein (LDL) particle size. The purpose of this hospital-based longitudinal study was to clarify the causal relationship between changes in the LCAT activity and changes in the LDL-particle size. Methods The subjects were a total of 335 patients, derived from our previous study cohort, with one or more risk factors for atherosclerotic cardiovascular disease (ASCVD). For this study, we measured the LDL-particle size (relative LDL migration [LDL-Rm value]) by polyacrylamide gel electrophoresis in the subjects, along with the changes in the LCAT activity, at the end of a follow-up period of at least 1 year. Results The results revealed that the absolute change (Δ) in the LDL-particle size increased significantly as the quartile of Δ LCAT activity increased (p = 0.01). A multi-logistic regression adjusted-analysis revealed that Δ LCAT activity in the fourth quartile as compared to that in the first quartile was independently predictive of an increased LDL-particle size (odds ratio [95% confidence interval]: 2.03 [1.02/4.04], p = 0.04). Moreover, the ∆ LCAT activity was also positively correlated with ∆ TRL-related markers (i.e., TG, remnant particle-like cholesterol [RLP-C], apolipoprotein B, apolipoprotein C-2, and apolipoprotein C-3). Conclusions The results lend support to the hypothesis that increased LCAT activity may be associated with increased formation of TRLs, leading to a reduction in the LDL-particle size in patients at a high risk for ASCVD. To reduce the risk of ASCVD, it may be important to focus not only on the quantitative changes in the serum LDL-cholesterol levels, but also on the LCAT activity. Trial registration UMIN (https://upload.umin.ac.jp/cgi-bin/ctr/ctr_reg_list.cgi) Study ID: UMIN000033228 retrospectively registered 2 July 2018.